Status of Mulberry and Willow Inventory for Sports Goods Industry - Pant, M. M.; Chandola, L. P. (Indian Forester, 1978)
Irrigated Mulberry plantations, both for sericulture and Sports Goods Industries should be raised separately. Special funds need to be provided so that Mulberry plantations can be maintained like orchards. Planting of Mulberry trees can also be integrated with Social/Farm Forestry Schemes and Van Mahotsava. The plantations should be in the close proximity of the existing industrial belt. Centrally added Scheme for raising plantations for Sports Goods Industry- Mulberry in particular-needs to be prepared in consultation with Punjab and U.P. States and the concerned officials. Relaxations regarding the Inter-state movements of wood resources would help considerably in easing the present situation in Punjab and Uttar Pradesh. The States need to be requested to maintain a continuous inventory of the existing growing stock for the sports goods and other industries. The factory owners should indicate their annual demand of various species of wood and the prices they can pay. Without this data base, it is impossible to get a realistic picture of the industry.